The Optimization of Investigation by Satreskrim Polres Boyolali in Discovering Criminal Actions of Fraud through Electronic Media - Ariel Ginting (Akademi Kepolisian Republik Indonesia, 2023)
Each year, many individuals fall victim to internet fraud, but few opt to report it. The number of reported instances of fraud has increased, yet this trend persists. This study aims to find and examine how officers in the Boyolali Police Satreskrim region handle fraud cases via social media, as well as the obstacles they experience in doing so. In order to obtain a clear and relevant image of criminal policy on the role of the police in combating criminal acts of fraud over the Internet, interview data and all other data were evaluated using qualitative analytical techniques to address the defined challenges. The optimization of Polri's social media fraud case management has not been completed successfully. This problem emerges because HR departments lack the knowledge and resources essential to achieve their goals and objectives. Due to the fact normally, only a few numbers of employee has had official training in IT, it is evident that investigators' expertise in cybercrime disclosure tactics and methods is significantly weak at this time. Challenges include the fact that the Boyolali Polda Criminal Investigation Unit's budget is not yet sufficient for operational activities of investigation and investigation of criminal acts, including uncovering cyber crimes, and that Satreskrim lacks the infrastructure to process data from Check Position, Call Detail Record (CDR), and SMS (Short Message Service), as well as the know-how to perform such tasks.